Implementation Of Decisions On Inheritance Disputes Resolved Through Mediation At The Lhoksukon Syar'iyah Court: Case Study On Decision Number: 493/PDT.G/2015/MS-LSK - Imamuddin Imamuddin; Sabarudin Sabarudin (AT-TAFAHUM: Journal of Law, 2017)
The division of inheritance sometimes runs smoothly without any dispute at all, sometimes it must go through a dispute. The division of inheritance that is carried out through a dispute can often be resolved through peace but sometimes it must take legal action through a lawsuit to the court. The division of inheritance that runs without dispute also needs to be determined by the court, this is to avoid undesirable things. This type of research is normative legal research conducted at the Lhoksukon Syar'iah Court. The nature of this research is descriptive, namely defining systematically, factually and accurately which focuses on discussing the implementation of decisions on inheritance disputes resolved through mediation at the Lhoksukon Syar'iah Court. The theory used in writing this thesis is maslahah. The results of the study indicate that the submission of the lawsuit uses a request method addressed to the Chief Justice of the Court. The mediation resume is formulated by the parties immediately after the case title hearing and discussed with the Mediator during the first mediation, the Mediator reports it to the Case Examining Judge in writing by attaching the peace agreement. The examining judge issued a decision to the parties to the case in the form of an order to comply with the contents of the agreement in the peace deed and to pay court costs.